Impact of the Healthy Eating and Exercise Lifestyle Programme on depressive symptoms in overweight people with heart disease and diabetes. (September 2014) - Gallagher, Robyn; Zelestis, Elizabeth; Hollams, Dan; Denney-Wilson, Elizabeth; Kirkness, Ann
Background: The Healthy Eating and Exercise Lifestyle Program (HEELP) is a secondary risk factor intervention programme for people with heart disease and/or type 2 diabetes, which has proven benefits for weight loss and exercise. This secondary analysis evaluated the effects of HEELP on achieving recommended levels of exercise and the prevalence of depressive symptoms, and whether meeting exercise recommendations had an independent effect on depressive symptoms. Design: A randomized parallel controlled trial of patients ( n = 147) with body mass index 27–39 kg/m 2 were recruited from cardiac rehabilitation and diabetes education programmes. Methods: HEELP participants received a 16-week group-based lifestyle intervention of twice-weekly supervised exercise and five information sessions; the control group received usual care. At 16 weeks, achievement of recommended levels of exercise (≥5 days/week, moderate or higher intensity, and total duration of ≥150 minutes/week) and depressive symptoms (Hospital Anxiety and Depression Scale) were assessed. Results: More HEELP participants met the recommendations for exercise frequency (71 vs. 50%, p = 0.036), intensity (76 vs. 60%, p = 0.05), and total duration (65 vs. 43%, p = 0.047). The prevalence of depressive symptoms in HEELP was half that of the control group (17 vs. 34%; OR 0.397, 95% CI 0.18–0.86). Participants who met recommendations for total duration of exercise were less likely to report depressive symptoms (OR 0.29, 95% CI 0.112–0.717) after adjusting for treatment group and weight change. Conclusions: A group-based lifestyle intervention improves exercise and reduces depressive symptoms despite multiple risk factors.